Space-vector-modulated three-level inverters with a single Z-source network - Effah, Francis Boafo; Wheeler, Patrick; Clare, Jon C.; Watson, Alan James (IEEE, 2012)
The Z-source inverter is a relatively recent converter topology that exhibits both voltage-buck and voltage-boost capability. The Z-source concept can be applied to all dc-to-ac, ac-to-dc, ac-to-ac, and dc-to-dc power conversion whether two-level or multilevel. However, multilevel converters offer many benefits for higher power applications. Previous publications have shown the control of a Z-source neutral point clamped inverter using the carrier based modulation technique. This paper presents the control of a Z-source neutral point clamped inverter using the space vector modulation technique. This gives a number of benefits, both in terms of implementation and harmonic performance. The adopted approach enables the operation of the Z-source arrangement to be optimised and implemented digitally without introducing any extra commutations. The proposed techniques are demonstrated both in simulation and through experimental results from a prototype converter.